การเมืองในเรื่องการออกเอกสารสิทธิในที่ดิน - สุจิต จงประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
This thesis aims at studying criteria, methods and conditions of the land title issurance in the Nongkai province area, which are related to an exercise of power and influence embedded in the political process. Clearly, its focus is the politics of land title deed issuing. The study therefore basically hypothesizes that political influence has a considerable effect on criteria considerations of giving out land title and government policy changes which in turn asserts effective impact on the land to right and ownership system serving the interests of both concerned politicians and influential persons. The methodology of this study is based on a combination of document analysis and survey research strategies, plus interviews. Factual data collected from document are analyzed pointing to land title problems in the Nongkai province area. Together with the document analysis, the study make use of key people interviews, including Department of Land (DOL) executives, members of both factual and disciplinary investigation committees. These fact-based and attitudinal data of the investigations are crucial to this study. The main finding of this study clearly indicates that important factors causing deviated driteria, regulation, and law, thus creating problems in giving out the land title deed in the Nongkai province area are interventions of the politicians who have power and influence on the administration procedures and responsible bureaucrats. These politicians could give benefits both tangibly and intangibly to DOC officials, thus causing adverse impact on the organ of the state dealing with land title deed issurance.